ChemInform Abstract: Aspterpenacids A and B, Two Sesterterpenoids from a Mangrove Endophytic Fungus Aspergillus terreus H010 - Liu, Zhaoming; Chen, Yan; Chen, Senhua; Liu, Yayue; Lu, Yongjun; Chen, Dongni; Lin, Yongcheng; Huang, Xishan; She, Zhigang (ChemInform, 2016)
The title compounds (Ia) and (Ib) possess a novel carbocyclic skeleton, represented by an unprecedented ring system.